The Influence Of Hrm Practices On Job Satisfaction - The Mediating Role Of Organizational Commitment: Case Of Federal Authority For Identity And Citizenship (ICA) UAE - et. al., Mohammad Hassan Alhammadi , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The impact of HRM practices on employee satisfaction has been a leading area of research in the developed world for many years, while organizational commitment has not been studies in government sector in Unite Arab Emirates (UAE).The aim of this study is to examine the mediation role of organizational commitment on the association between HRM practices and job satisfactionin Federal Authority for Identity and Citizenship (ICA) in UAE using quantitative methods. The result of this study showed a high degree of model fit between HRM practices, organizational commitment, and job satisfaction as well as organizational commitment partially mediates the relationship between HRM practice and job satisfaction. This result lead to a final conclusion that HRM practices, organizational commitment, and job satisfaction are fundamental variables to the success of public and private organizations. Various organizations can benefit from the outcome of this study by knowing the employees level of satisfaction. For the employees indirectly helps them to convey their expectations regard this project highlights the scope for future improvement in above requirements provided to the employees.